Toll-like receptors as developmental tools that regulate neurogenesis during development: an update - Barak, Boaz; Feldman, Noa; Okun, Eitan (Frontiers in Neuroscience, 2014)
Neurogenesis, the process of generating new neurons in the brain, fascinates researchers for its promise to affect multiple cognitive and functional processes in both health and disease. Many cellular pathways are involved in the regulation of neurogenesis, a complexity exemplified by the extensive regulation of this process during brain development. Toll-like receptors (TLRs), hallmarks of innate immunity are increasingly implemented in various central nervous system plasticity-related processes including neurogenesis. As TLRs are involved in neurodegenerative disorders, understanding the involvement of TLRs in neurogenesis may hold keys for future therapeutic interventions. Herein, we describe the current knowledge on the involvement of TLRs in neurogenesis and neuronal plasticity and point to current knowledge gaps in the field.